Exergy analysis of refrigerator for a three steps freezing process. Issue 1 (1st January 2019) - Sukusno, Paulus; Setiawan, Radite Praeko Agus; Purwanto, Yohanes Aris; Tambunan, Armansyah Halomoan
Abstract: Temperature difference between the evaporator and the product during a freezing process is one of the sources of irreversibility. Application of three-steps evaporator temperature during the freezing course is expected to lower the irreversibility and improve energy efficiency of the system. The purpose of this research is to analyze the energy and exergy efficiency of a refrigeration system with three-steps temperature for freezing process. The experiment was conducted using laboratory scale freezer equipped with three expansion valves to provide the required temperature level at each step. Thermodynamic properties of the refrigerant during the process were obtained by using Engineering Equation Solver (EES). The results show that freezing with three temperature steps gave total COP of 2.66, higher than COP of the fixed temperature process, which was 2.40. Exergy analysis shows that average irreversibility of the compressor with stepping temperature operation was higher than that of fixed temperature operation, which was mainly affected by the higher irreversibility during the first step of the stepping temperature operation. It is concluded that compressor work needs to be adjusted to the real work requirement by using an equipment such as inverter in order to take advantage of the stepping temperature operation in terms of more efficient use of power by the compressor.